2020
DOI: 10.1186/s12935-020-01602-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PKP 2/3 as potential biomarkers of ovarian cancer based on bioinformatics and experiments

Abstract: Background Plakophilins (PKPs) are widely involved in gene transcription, translation, and signal transduction, playing a crucial role in tumorigenesis and progression. However, the function and potential mechanism of PKP1/2/3 in ovarian cancer (OC) remains unclear. It’s of great value to explore the expression and prognostic values of PKP1/2/3 and their potential mechanisms, immune infiltration in OC. Methods The expression levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“… 24 PKP2 was elucidated to initially affect tumorigenesis, aggressiveness, malignant biological behavior, and immune infiltration of ovarian cancer. 25 These results correspond to the risk ratio of the feature genes we analyzed, whereas the observation of TMPRSS11F and MARCH4 is less explored. KRT81, a hair keratin, has become a biomarker of breast cancer and was revealed to promote cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“… 24 PKP2 was elucidated to initially affect tumorigenesis, aggressiveness, malignant biological behavior, and immune infiltration of ovarian cancer. 25 These results correspond to the risk ratio of the feature genes we analyzed, whereas the observation of TMPRSS11F and MARCH4 is less explored. KRT81, a hair keratin, has become a biomarker of breast cancer and was revealed to promote cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 82%
“…PKP2, a member of the p120ctn family of cell adhesion molecules, enhances cell proliferation, migration, and invasion by activating the EGFR signaling pathway in LUAD 24 . PKP2 was elucidated to initially affect tumorigenesis, aggressiveness, malignant biological behavior, and immune infiltration of ovarian cancer 25 …”
Section: Discussionmentioning
confidence: 99%
“…Plakophilin-2 ( PKP2 ) was initially identified as a desmosomal protein, but further studies have revealed that it is localized in the cytoplasm and nucleus as well [ 28 ]. PKP2 expression is upregulated in many cancers, such as lung [ 29 ], ovarian [ 30 ], glioma [ 31 ], and bladder cancers [ 32 ]. Increased PKP2 expression was also related to a malignant phenotype and poor prognosis in some cancers [ 29 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…PKP2 has been reported to be overexpressed in all adenocarcinomas [ 25 , 27 ]. High PKP2 expression was reported to be involved in the development of various cancers, including bladder [ 38 ], lung [ 39 ], and ovarian cancers [ 24 ]. However, the role of PKP2 in OS has rarely been studied, except for that reported by He et al .…”
Section: Discussionmentioning
confidence: 99%
“…We uploaded the top 50 most upregulated genes in OS from the GSE11416 data series to the string database, and identified 17 that were shown to interact closely ( Figure 1a ). Among the 17 genes, we found that PKP2 was upregulated in cancers and accelerated cancer development [ 24–28 ]. Nonetheless, only one study has revealed the positive role of PKP2 in OS [ 29 ].…”
Section: Methodsmentioning
confidence: 99%